Entre nos - La Morte, Gloria; Mendoza, Paola; Villada Lopez, Sebastian; Montana Cortez, Laura; IndiePix (Firm); Soundview Media Partners (New York : IndiePix, 2009)
Entre Nos tells the true story of a woman's struggle to survive in New York City with her two children after being abandoned by her husband. --
Originally released as a motion picture in 2009.
"Inspired by a true story."
Paola Mendoza, Sebastian Villada Lopez, Laura Montana Cortez, Anthony Chisholm, Andres Munar, Sarita Choudhury.
Cinematographer, Bradford Young ; editor, Gloria La Morte ; music, Gil Talmi.
In Spanish; with English subtitles.
Winner Best Film, Traverse City Film Festival Jury Award 2009
Keywords: Immigrants -- New York (State) -- New York -- Drama; Single mothers -- New York (State) -- New York -- Drama; Colombians -- New York (State) -- New York -- Drama; Feature films; Documentary films; Nonfiction films; Internet videos; Streaming video